The intensity of ethylene release by soybean plants under the influence of fungicides in the early stages of legume-rhizobial symbiosis - T. P. Mamenko; S. Y. Kots; Y. O. Khomenko (Regulatory Mechanisms in Biosystems, 2020)
The effect of pre-sowing treatment of soybean seeds with fungicides on the intensity of ethylene release, the processes of nodulation and nitrogen fixation in different symbiotic systems in the early stages of ontogenesis were investigated. The objects of the study were selected symbiotic systems formed with the participation of soybean (Glycine max (L.) Merr.) Diamond variety, strains Bradyrhizobium japonicum 634b (active, virulent) and 604k (inactive, highly virulent) and fungicides Maxim XL 035 PS (fludioxonil, 25 g/L, metalaxyl, 10 g/L), and Standak Top (fipronil, 250 g/L, thiophanate methyl, 225 g/L, piraclostrobin, 25 g/L). Before sowing, the seeds of soybean were treated with solutions of fungicides, calculated on the basis of one rate of expenditure of the active substance of each preparation indicated by the producer per ton of seed. One part of the seeds treated with fungicides was inoculated with rhizobium culture for 1 h (the titre of bacteria was 107 cells/mL). To conduct the research we used microbiological, physiological, biochemical methods, gas chromatography and spectrophotometry. It is found that, regardless of the effectiveness of soybean rhizobial symbiosis, the highest level of ethylene release by plants was observed in the stages of primordial leaf and first true leaf. This is due to the initial processes of nodulation – the laying of nodule primordia and the active formation of nodules on the roots of soybeans. The results show that with the participation of fungicides in different symbiotic systems, there are characteristic changes in phytohormone synthesis in the primordial leaf stage, when the nodule primordia are planted on the root system of plants. In particular, in the ineffective symbiotic system, the intensity of phytohormone release decreases, while in the effective symbiotic system it increases. At the same time, a decrease in the number of nodules on soybean roots inoculated with an inactive highly virulent rhizobia 604k strain due to the action of fungicides and an increase in their number in variants with co-treatment of fungicides and active virulent strain 634b into the stage of the second true leaf were revealed. It was shown that despite a decrease in the mass of root nodules, there is an increase in their nitrogen-fixing activity in an effective symbiotic system with the participation of fungicides in the stage of the second true leaf. The highest intensity of ethylene release in both symbiotic systems was recorded in the stage of the first true leaf, which decreased in the stage of the second true leaf and was independent of the nature of the action of the active substances of fungicides. The obtained data prove that the action of fungicides changes the synthesis of ethylene by soybean plants, as well as the processes of nodulation and nitrogen fixation, which depend on the efficiency of the formed soybean-rhizobial systems and their ability to realize their symbiotic potential under appropriate growing conditions.